An adaptive collocation method for structural fuzzy uncertainty analysis. Issue 9 (30th April 2020) - Wang, Lei; Xiong, Chuang; Shi, Qinghe
Abstract : Purpose: Considering that uncertain factors widely exist in engineering practice, an adaptive collocation method (ACM) is developed for the structural fuzzy uncertainty analysis. Design/methodology/approach: ACM arranges points in the axis of the membership adaptively. Through the adaptive collocation procedure, ACM can arrange more points in the axis of the membership where the membership function changes sharply and fewer points in the axis of the membership where the membership function changes slowly. At each point arranged in the axis of the membership, the level-cut strategy is used to obtain the cut-level interval of the uncertain variables; besides, the vertex method and the Chebyshev interval uncertainty analysis method are used to conduct the cut-level interval uncertainty analysis. Findings: The proposed ACM has a high accuracy without too much additional computational efforts. Originality/value: A novel ACM is developed for the structural fuzzy uncertainty analysis.